Digital CultureÂ DevelopmentÂ of the Library Agency of East Kalimantan Province : An Autoethnography Note - Yoganingrum, Ambar; Taufik, Taufik (Komunitas, 2018)
The libraries must be able to transform into a digital library so they can build a digital society and serve the digital generation. Problems occur when the library itself fails to develop the digital culture of its employees which results in the failure of transformation into a digital library. This article is an experience in undergoing and observing the efforts of the Library of East Kalimantan Province to transform itself into a digital library. This effort has lasted until now, where one of the obstacles is that most employees are digital immigrant generations. Data collection was done by remembering and writing down the process from 1992 to the present. The analysis process was employed by looking at every meaning of the writing in the diary (content analysis). In 2015, The Library Agency of East Kalimantan Province of Indonesia obtained an A rating in the management of digital libraries from the National Library of Indonesia. There are three factors that need to be considered in the transformation effort, namely formal and informal education for employees, leadership, and employee mental development. This article is beneficial for government institutions in facing the constraints of transformation into digital libraries, especially dealing with employees who are mostly immigrant digital generations.